Kunst & Zwalm 2009. - Kockelkorn, René; Van Mulders, Wim; Exhibition. Kunst & Zwalm 2009. Zwalm. Zwalmstreek. Boem vzw Zwalm. 2009-08-29. 2009-09-13 (Zwalm : Boem vzw Zwalm, 2009)
Jacobs, Roel ; Quetsch, Roland ; Nys, Sophie ; Feipel, Martine ; Bechameil, Jean ; Dheedene, Stefaan ; Schacht, Kelly ; Vangrunderbeek, Dimitri ; Frantz, Jerry ; Ewen, Luc ; Van San, Tamara ; Frantzen, Christian ; Manders, Mark ; Moens, Rik
CD in speciale kast
biog. p. 92-93
Duits
Nederlands
boek
Keywords: Zwalm